Dziesięć lat rynku obligacji komunalnych w Polsce - doświadczenia i perspektywy - Kozuń-Cieślak, Grażyna (Ten Years of the Municipal Bond Market in Poland - Experience and Perspectives, 2007)
Decentralization of the nation's functions made the municipal governments' administrators use particularly the managing skills especially in the context of a very difficult choice between the socially useful and the economically explained. The knowledge of modern finance management methods and the ways of getting financial sources is more important nowadays because in current situation of public finances quick compensation for many years' developmental unfulfilled tasks arising from economical under-investment is possible only through accomplishing investments that use outside financial sources. In the present report the attention has been focused on the problems connected with using bonds issues as a financial source by communes. The subject has been formulated from the quantitative and the qualitative point of view of the municipal bonds' market estimation, which allowed to predict the position of this finance instrument in governing the debt by the municipal government units in the future.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 488-497